ENGLISH COMMUNICATION PROGRAM: SCHOOL'S EFFORT IN FACILITATING STUDENTS' SPEAKING - Yeni, Melda; Syafrizal, Syafrizal; Ridhwan, Muhammad; Cholid, Muhammad; Herawati, Nana (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2022)
The aim of this research is to discover about the communication program held by SMAN 1 Tembilahan in order to improve students' speaking skills. The qualitative data was gathered and a Google form questionnaire was distributed to get the data dealong with the purpose above. This study sample consists of 3 English teachers from SMAN 1 Tembilahan who actively guide their students in English extracurricular. Based on the data result, there are two programs that can help students improve their speaking skill in this school. The one which facilitates students to have much exercises; English Club and another one facilitates students to compate each other at the end of every semester; English performance competition. Students in english club program learn and practice debate, speech, and 4 main skills (listening, writing, reading, and speaking). Meanwhile, in the english performance competition, students compete in debate and speech presentation.